1976
DOI: 10.1073/pnas.73.5.1476
|View full text |Cite
|
Sign up to set email alerts
|

Human pituitary growth hormone: restoration of full biological activity by noncovalent interaction of two fragments of the hormone.

Abstract: The NH2-terminal 134 amino-acid fragment of the reduced-carbamidomethylated human somatotropin molecule is found to react noncovalently with the COOS-terminal 51 amino-adid fragment in solutions of pH 8.4 at 20 to restore full biological activity as evidenced by the rat tibia and pigeon crop-sac assays. In addition, circular dichroism spectra of the recombinant show the conformation to be completely repaired in comparison with that of the native hormone.The use of plasmin for the partial digestion of somatotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…It is possible that substitutions of Aspl'3 and Ile'79 by His and Met, respectively, in the hCS structure prevent the generation of full biological activity. These results demonstrate that the three-di- (2,8).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…It is possible that substitutions of Aspl'3 and Ile'79 by His and Met, respectively, in the hCS structure prevent the generation of full biological activity. These results demonstrate that the three-di- (2,8).…”
Section: Resultssupporting
confidence: 57%
“…It is evident that recombinant I had 50% of the potency of hGH, whereas recombinant II was considerably less active. (2,4) in that the COGH-terminal fragment was first dissolved in 1 M NH40H to give a clear solution before mixing with the NH2-terminal fragment. This gives rise to a better yield of purified recombinant product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The (9). The complementation reactions were carried out by published procedures (2,10). Briefly, 3 (9).…”
Section: Methodsmentioning
confidence: 99%
“…1), [Carbamoylmethylcys- give a recombinant protein with the full biological activities (2,3) of the natural hormone. Subsequently, it was found that complementation of the natural NH2-terminal fragment with the synthetic COOH-terminal fragment or its synthetic analogs gave rise to fully active recombinants (4,5).…”
mentioning
confidence: 99%